A tumor immune microenvironment gene expression signature for predicting prognosis, immunotherapy efficacy, and drug candidates in triple-negative breast cancer - Bai, Li; Zhou, Ziyu; Yu, Qingqing; Ye, Zhen; Li, Qingzhou; Li, Shengrong; Li, Congcong; Hu, Yu; Hu, Yunjie; Tai, Xinran; Xiang, Lei; Sun, Sijuan; et al. (Frontiers in Immunology, 2025)
BackgroundImmunotherapy has transformed cancer treatment, but its efficacy remains limited in patients with immunologically “cold” tumors. Triple-negative breast cancer (TNBC), despite elevated PD-L1 expression and high tumor mutation burden, often exhibits poor T cell infiltration, rendering it largely unresponsive to immune checkpoint blockade. Overcoming the immunosuppressive tumor immune microenvironment (TIME) remains a major challenge in oncology.MethodsWe defined a tumor immune microenvironment gene expression signature (TIME-GES) through transcriptomic analysis of clinical samples. Its performance and relevance were evaluated using representative approaches including enrichment analysis, immune infiltration profiling, receiver operating characteristic analysis, and survival assessment. Based on TIME-GES, we screened 1,865 natural compounds and identified Nitidine Chloride (NCD) as a potential modulator in TNBC. In vivo efficacy of NCD against TNBC was examined by representative assays such as flow cytometry and immunofluorescence. Mechanistic insights into TNBC treatment via TIME-GES were explored through RNA sequencing, quantitative PCR, Western blotting, and cellular thermal shift assay.ResultsTIME-GES effectively characterizes the tumor immune microenvironment across diverse cancer types. It reliably distinguishes tumor immune phenotypes and predicts patient responses to immunotherapy. Moreover, TIME-GES is strongly associated with survival outcomes in patients receiving immunotherapy and remains a significant prognostic marker for overall survival and mortality in TCGA pan-cancer cohorts, regardless of treatment. Guided by TIME-GES, NCD was identified from a natural product library and shown to modulate TIME-GES gene expression and significantly inhibit TNBC growth in vivo. NCD enhances CD8+ T cell–mediated antitumor immunity by upregulating TIME-GES genes and targeting the JAK2-STAT3 signaling pathway, resulting in suppressed tumor growth and reprogramming of the TIME toward a more immunologically active, “hot” phenotype.ConclusionThis study identified TIME-GES as a novel biomarker capable of distinguishing tumor immune phenotypes, predicting immunotherapy response, and evaluating prognosis in TNBC. Furthermore, TIME-GES-guided screening led to the discovery of NCD, a promising immunomodulatory agent that reprograms the TIME and enhances anti-tumor immunity in TNBC. This study offers both a robust immune gene signature and a candidate therapeutic to improve immunotherapy outcomes in TNBC.